Review paperChoice of the β-adrenergic receptors blockers for patients with diabetes mellitus - Szczeklik-Kumala, Zofia; Czech, Anna (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2010)
The significantly increased incidence and morbidity due to high blond pressure and cardio-vascular syndrome as characteristic for the subpopulation with diabetes mellitus is the cause that the choice of the proper β-blocker has the important practical significance. It is based on balancing the advantages and unwanted side effects of the particular β-blockers. Persons with diabetes mellitus are more sensitive to many negative influences of this large group of drugs. Due to this fact in diabetes mellitus it is mercenary as well as the specific determination of the aims of therapy, individual pattern of diabetes mellitus, methods of monitoring the therapy also the use of evidence-based selection of drug. In this respect many advantages are presorted by carvedilol.